The Role of Glia in the Peripheral and Central Auditory System Following Noise Overexposure: Contribution of TNF-α and IL-1β to the Pathogenesis of Hearing Loss - Fuentes-Santamaría, Verónica; Alvarado, Juan Carlos; Melgar-Rojas, Pedro; Gabaldón-Ull, María C.; Miller, Josef M.; Juiz, José M. (Frontiers in Neuroanatomy, 2017)
Repeated noise exposure induces inflammation and cellular adaptations in the peripheral and central auditory system resulting in pathophysiology of hearing loss. In this study, we analyzed the mechanisms by which noise-induced inflammatory-related events in the cochlea activate glial-mediated cellular responses in the cochlear nucleus (CN), the first relay station of the auditory pathway. The auditory function, glial activation, modifications in gene expression and protein levels of inflammatory mediators and ultrastructural changes in glial-neuronal interactions were assessed in rats exposed to broadband noise (0.5–32 kHz, 118 dB SPL) for 4h/day during four consecutive days to induce long-lasting hearing damage. Noise-exposed rats developed a permanent threshold shift which was associated with hair cell loss and reactive glia. Noise-induced microglial activation peaked in the cochlea between 1 and 10D post-lesion; their activation in the CN was more prolonged reaching maximum levels at 30D post-exposure. RT-PCR analyses of inflammatory-related genes expression in the cochlea demonstrated significant increases in the mRNA expression levels of pro- and anti-inflammatory cytokines, inducible nitric oxide synthase, intercellular adhesion molecule and tissue inhibitor of metalloproteinase-1 at 1 and 10D post-exposure. In noise-exposed cochleae, interleukin-1β (IL-1β) and tumor necrosis factor α (TNF-α) were upregulated by reactive microglia, fibrocytes and neurons at all time points examined. In the CN, however, neurons were the sole source of these cytokines. These observations suggest that noise exposure causes peripheral and central inflammatory reactions in which TNF-α and IL-1β are implicated in regulating the initiation and progression of noise-induced hearing loss.